Time-domain and spectral properties of pulsars at 154 MHz. Issue 1 (31st May 2016) - Bell, M. E.; Murphy, Tara; Johnston, S.; Kaplan, D. L.; Croft, S.; Hancock, P.; Callingham, J. R.; Zic, A.; Dobie, D.; Swiggum, J. K.; Rowlinson, A.; Hurley-Walker, N.; et al.
Abstract: We present 154 MHz Murchison Widefield Array imaging observations and variability information for a sample of pulsars. Over the declination range −80° < δ < 10°, we detect 17 known pulsars with mean flux density greater than 0.3 Jy. We explore the variability properties of this sample on time-scales of minutes to years. For three of these pulsars, PSR J0953+0755, PSR J0437−4715, and PSR J0630−2834, we observe interstellar scintillation and variability on time-scales of greater than 2 min. One further pulsar, PSR J0034−0721, showed significant variability, the physical origins of which are difficult to determine. The dynamic spectra for PSR J0953+0755 and PSR J0437−4715 show discrete time and frequency structure consistent with diffractive interstellar scintillation and we present the scintillation bandwidth and time-scales from these observations. The remaining pulsars within our sample were statistically non-variable. We also explore the spectral properties of this sample and find spectral curvature in pulsars PSR J0835−4510, PSR J1752−2806, and PSR J0437−4715.